A review of calixarene langmuirblodgett thin film characteristics for nanosensor applications - Mohd Syahriman Mohd Azmi (Tanjong Malim, 2020)
A review of calixarene langmuirblodgett thin film characteristics for nanosensor applications by Mohd Syahriman Mohd Azmi